2004
DOI: 10.1152/ajpheart.00768.2003
|View full text |Cite
|
Sign up to set email alerts
|

Infarction alters both the distribution and noradrenergic properties of cardiac sympathetic neurons

Abstract: Regional changes occur in the sympathetic innervation of the heart after myocardial infarction (MI), including loss of norepinephrine (NE) uptake and depletion of neuronal NE. This apparent denervation is accompanied by increased cardiac NE spillover. One potential explanation for these apparently contradictory findings is that the sympathetic neurons innervating the heart are exposed to environmental stimuli that alter neuronal function. To understand the changes that occur in the innervation of the heart aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
105
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(117 citation statements)
references
References 42 publications
8
105
0
Order By: Relevance
“…Although the present study confirms peri-infarct hyperinnervation (Cao, et al, 2000a;Cao, et al, 2000b), other studies have reported reduced cardiac sympathetic innervation after infarction (Barber, et al, 1983;Igawa, et al, 2000;Li, et al, 2004). These differences may be related to the extent of infarction as larger infarcts can result in frank congestive heart failure, and this has been linked to cardiac NGF depletion and diminished sympathetic axon density (Kaye, et al, 2000;Qin, et al, 2002).…”
Section: Selectivity Of Post-infarct Hyperinnervationsupporting
confidence: 63%
See 3 more Smart Citations
“…Although the present study confirms peri-infarct hyperinnervation (Cao, et al, 2000a;Cao, et al, 2000b), other studies have reported reduced cardiac sympathetic innervation after infarction (Barber, et al, 1983;Igawa, et al, 2000;Li, et al, 2004). These differences may be related to the extent of infarction as larger infarcts can result in frank congestive heart failure, and this has been linked to cardiac NGF depletion and diminished sympathetic axon density (Kaye, et al, 2000;Qin, et al, 2002).…”
Section: Selectivity Of Post-infarct Hyperinnervationsupporting
confidence: 63%
“…Following ischemia-reperfusion, for example, an acute neurochemical change occurs in sympathetic innervation as a consequence of inflammatory cytokine release (Li, et al, 2004). Denervation in the apex of the heart after ischemia-reperfusion can also occur as the infarct may disrupt passage of sympathetic nerves (Barber, et al, 1983).…”
Section: Selectivity Of Post-infarct Hyperinnervationmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental investigations of rat cardiac sympathetic neurons following myocardial infarction revealed that infarction altered both the distribution and noradrenergic properties of cardiac sympathetic neurons. Apparent sympathetic denervation of the heart after myocardial infarction is accompanied by the loss of norepinephrine uptake and the depletion of neuronal norepinephrine (9,10). Another experimental study revealed that target deprivation produced by visual cortex ablation caused the death of geniculate neurons in the dorsal lateral geniculate nucleus by an apoptotic process after axotomy (11).…”
mentioning
confidence: 99%